Применим основное тригонометрическое тождество:
Sin²A+ Cos²A= 1
Cos²A= 1- Sin²A
Подставим известные значения:
Cos²A= 1- ()²
Cos²A= -
Cos²A=
CosA=
ответ: CosA= .
cos²α = 1 - sin²α
cos(α) = √(1 - (12/13)²) = 5/13
ответ: 5/13
Применим основное тригонометрическое тождество:
Sin²A+ Cos²A= 1
Cos²A= 1- Sin²A
Подставим известные значения:
Cos²A= 1- (
)²
Cos²A=
- ![\frac{144}{169}](/tpl/images/0130/8816/8d8dd.png)
Cos²A=![\frac{25}{169}](/tpl/images/0130/8816/194b7.png)
CosA=![\frac{5}{13}](/tpl/images/0130/8816/383bf.png)
ответ: CosA=
.
cos²α = 1 - sin²α
cos(α) = √(1 - (12/13)²) = 5/13
ответ: 5/13